ANALISIS PENGARUH UKURAN PERUSAHAAN TERHADAP KINERJA INTELLECTUAL CAPITAL DENGAN STRUKTUR KEPEMILIKAN SEBAGAI VARIABEL MODERATING - Indra Fery Irawan; Tarmizi Achmad (Diponegoro Journal of Accounting, 2014)
This study aims to empirically examine the effect of firm size on the performance of the role of intellectual capital and ownership structure as a moderating variable in the relationship between firm size and performance of intellectual capital. Ownership structure used in this study is the family ownership structure and institutional ownership strukutur measured using the proportion of the number of shares owned by families and institutions . While firm size is measured by using the total number of company assets and intellectual capital performance is measured using VAIC ™ method developed by Pulic (1998 ) .This study used a sample of banking companies listed on the Stock Exchange periode 2007-2011 using purposive sampling method. The data used were obtained from the annual financial statements of banking companies listed on the Stock Exchange. There are 31 companies and 136 observations over the years 2007-2011. The method of analysis used in this study is multiple regression analysis . This method was chosen because all of the data is matrix variable.In the statistical results of the study found that company size does not significantly affect the performance of intellectual capital . However, in this study also found that both the family ownership structure and institutional ownership significantly moderate the relationship between firm size on the performance of intellectual capital.